4D flow magnetic resonance imaging to assess left atrial haemodynamics in healthy and hypertrophic subjects. (8th February 2021) - Morales Ferez, X; Mill, J; Delso, G; Sitges, M; Doltra, A; Loncaric, F; Camara, O; Bijnens, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): - University, research centre and hospital foundation grants for the contracting of new research staff (FI 2020) - Spanish Ministry of Economy and Competitiveness Retos investigacion project Introduction: The assessment of the left atrium (LA) haemodynamics is key to better understand the development of LA-related pathological processes. In this regard 4D flow magnetic resonance imaging (MRI) can provide complementary information to standard Doppler echocardiographic studies and identify complex blood flow patterns. Yet, until recently, the left atrium (LA) has been largely left aside in 4D flow MRI studies. Purpose: We aimed at assessing the LA haemodynamics of healthy and hypertrophic cardiomyopathy (HCM) subjects with a qualitative visualization of flow patterns and deriving quantitative indices related to ventricular dysfunction from pulmonary veins (PV)  and mitral valve (MV) velocity profiles. Methods: Segmentation was performed directly over 4D flow angiograms. A total of 20 cases were processed, 11 healthy and 9 HCM subjects. 4D velocity matrices were masked with the segmented mask to isolate LA haemodynamics. Velocity profiles were then obtained in the PV and MV and integrated over planes perpendicular to the lumen of the vessels to create velocity spectrograms. Fourier spectral analysis was applied to the velocity curves to highlight differences that might go unnoticed in the time domain. In addition, the Q-Criterion was computed for vortex identification, visually inspecting both cohorts across the whole cardiac cycle. Results: Fourier spectral analysis of the velocity curves suggested that overall, healthy patients have higher dynamic range of the velocity curves. It can be observed in Figure 1, that the usual E/A MV velocity pattern is preserved in 10 of the 11 healthy subjects while 5 of the HCM patients present significant alterations of said curve. In fact, patients 4, 6, 7 and 8 seem to present a 3 peaked MV velocity curve. The vortex analysis identified 3 main types of vortices in healthy subjects: a 'filling' systolic vortex (10/11) arising near the most dominant PV (usually the left superior PV) as seen in Figure 2; a conduit phase vortex (7/11), similar in nature to the preceding systolic vortex; and an E-wave vortex (9/11) attached to the LA ostium. Four of the HCM patients (out of the five with altered MV velocity profile) also showed a systolic vortex, but with more complex blood flow patterns and emerging far from the PVs. One of such vortices is shown in Figure 2, composed of two distinct eddies near the MV. The E-wave vortex was also observed but was less predominant than in healthy subjects (3/9). Conclusions: 4D Flow analysis of the LA is feasible and might hold promise in the understanding of the complex haemodynamics in ventricular dysfunction.